Autonomous learning in the face of the evolution of study modalities in higher education in Nicaragua - Salgado Aráuz, Georvany José (Scientific journal of social studies, 2024)
The evolution of autonomous learning due to the demands of new technologies and information in education. Exploring new trends in instructional design that encourage unlimited content and directions in learning, self-assessment and the use of cognitive activities that support a meaningful, collaborative, and experiential learning process. The essay also highlights the importance of autonomous and self-directed learning, which allows students to understand their cognitive and socio-affective processes. It discusses the importance of considering student learning styles, including visual, auditory, kinesthetic, and reading/writing when designing learning strategies. Finally, the essay emphasizes study modalities in higher education, including e-learning, m-learning, and b-learning, which combine elements of traditional and online learning methods. The essay concludes with the importance of teachers' and students' active and dynamic participation in using various technological tools that facilitate the learning process.
Keywords: Autonomous learning; study modalities; learning styles; instructional design